The hegemonic order in the 21st century - STANISLAW BIELEN (Сравнительная политика)
The concept of the hegemonic order in international relations is, on the one hand, related to the state-centric understanding of the international system, and on the other hand, to the challenging of the thesis of its polyarchism. While historic hegemonies never had a monopoly on exclusivity, theU.S.has achieved a clear and significant advantage over other powers. This was due to numerous reasons. The multidimensionality of theU.S.power means that no one else is able to match theU.S.in military, economic, technological, political, or cultural-civilizational and ideological terms. TheUnited Stateshas become the only power that can effectively stabilize or destabilize the existing global order. The biggest source of current concern is, on the one hand, a contestation ofU.S.hegemony in the world, and, on the other, its actual decline